Implemented Strategies in Business-to-Business Contexts - Woodside, A.G (Institutional Knowledge at Singapore Management University, 2012)
This chapter documents the contributions in the business-to-business (B2B) marketing–buying literature that focus on implemented strategies in specific contexts. Research on implemented strategies often includes thick descriptions of how things actually get done over a period of weeks, months, or years including how decision makers make sense of situations, go about processing information, make choices, interact with other decision makers, participate in specific actions, and interpret events and outcomes. Research on implemented strategies favors “direct research” (Mintzberg, 1979) that includes multiple face-to-face interviews of the same and different participants in B2B processes over the course of days, week, months, or years. Direct research is inherently inductive theory-building and case-based data driven in its theory-empirical approach. Direct research includes applying a number of possible research methods and results in a number of advances in B2B implemented-strategy-in-context theory.